2010
DOI: 10.3329/jhpn.v28i4.6045
|View full text |Cite
|
Sign up to set email alerts
|

Birth Preparedness and Complication Readiness among Slum Women in Indore City, India

Abstract: Three hundred twelve mothers of infants aged 2-4 months in 11 slums of Indore, India, were interviewed to assess birth preparedness and complication readiness (BPACR) among them. The mothers were asked whether they followed the desired four steps while pregnant: identified a trained birth attendant, identified a health facility, arranged for transport, and saved money for emergency. Taking at least three steps was considered being well-prepared. Taking two or less steps was considered being less-prepared. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

61
141
27

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(229 citation statements)
references
References 9 publications
(10 reference statements)
61
141
27
Order By: Relevance
“…The mothers who fulfilled at least four BP/CR practices were considered as 'Well prepared' and the rest of them were 'less prepared', similar to a previous study conducted. 17 Study was conducted in rural field practice areas under Rural Health Training Centre (RHTC), KAMSRC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mothers who fulfilled at least four BP/CR practices were considered as 'Well prepared' and the rest of them were 'less prepared', similar to a previous study conducted. 17 Study was conducted in rural field practice areas under Rural Health Training Centre (RHTC), KAMSRC.…”
Section: Methodsmentioning
confidence: 99%
“…Study conducted in Indore city reported that only 47.8% were well prepared Less than one third (29.5%) of respondents were well birth prepared. 17,19 In a study out of 371 pregnant mothers, only 133 (35.85%) were well prepared for child birth. 18 Pregnant women in the age group of >30 years, educational status of pregnant women and their husbands and joint family have significant associations for well birth preparedness and complication readiness (p<0.0005).…”
mentioning
confidence: 99%
“…Similar to other studies, we found that higher level of education is associated with birth preparedness and complication readiness. 6,7,[10][11][12][13][14] We attribute this to the fact that a woman who is educated is likely to understand more the health messages and apply the knowledge accordingly compared to an illiterate woman. 7,10,14 Contrary to studies in Kenya and Uganda, middle age rather than young age was associated with utilization of IBP.…”
Section: Determinants Of Ibp Utilizationmentioning
confidence: 99%
“…6,7,[10][11][12][13][14] We attribute this to the fact that a woman who is educated is likely to understand more the health messages and apply the knowledge accordingly compared to an illiterate woman. 7,10,14 Contrary to studies in Kenya and Uganda, middle age rather than young age was associated with utilization of IBP. 7,10 Perhaps this is because younger women were single whereas the middle-aged were mostly married; and being married is a factor associated with utilization of IBP.…”
Section: Determinants Of Ibp Utilizationmentioning
confidence: 99%
“…In the extant literature, however, operational definitions of BP/CR have varied widely, contributing to a diversity of approaches and little consistent evidence of intervention effectiveness or on essential elements of these interventions; some researchers have focused primarily on preparations for obstetric emergencies (e.g., heightening awareness of danger signs, identifying a facility where emergency obstetric care is available, setting aside money for an emergency, identifying a potential blood donor, and arranging for emergency transport; McPherson, Khadka, Moore, & Sharma, 2006;Moran et al, 2006;Mutiso, Qureshi, & Kinuthia, 2008). Other researchers have explored both complication readiness and planning for normal delivery without making a clear distinction between the two (Agarwal, Sethi, Srivastava, Jha, & Baqui, 2010;Ekabua et al, 2011;Hailu, Gebremariam, Alemseged, & Deribe, 2011;Kabakyenga, Ostergren, Turyakira, & Pettersson, 2012;Kakaire, Kaye, & Osinde, 2011;Magoma et al, 2013;Mullany, Becker, & Hindin, 2007;Turan, Tesfagiorghis, & Polan, 2011), and several have included women's use of antenatal care (ANC), the content of those consultations, or both, among measures of birth preparedness (Kakaire et al, 2011;Karkee, Lee, & Binns, 2013;McPherson et al, 2006).…”
mentioning
confidence: 99%